Brain Crosstalk with Other Organs in ICU Patient - Saran, Sai; Gurjar, Mohan (Journal of Neuroanaesthesiology and Critical Care, 2019)
Crosstalk between various organs exists in the human body. This can be part of physiological reflexes such as cardiac reflexes that protect the organs during stressful stimuli or can be part of pathological conditions where an insult to an organ releases cytokines that cause distant effects on other organs. In critically ill patients, these crosstalks are independent of pre-existing common risk factors or the presence of new risk exposure during the treatment. Crosstalk can manifest in series or parallel. The human brain, being a control center of the human body, does crosstalk with almost every organ in the body. In this narrative review, crosstalk of the brain with various organs and systems such as the heart, lungs, liver, kidneys, gut, muscle, bone, skin, adipose tissue, and immune system is being discussed along with clinical manifestations and management. Future research might help to target these pathological processes in preventing progression of single-organ dysfunction to multi-organ failures in critically ill patients.
Keywords: brain; crosstalk; multi-organ failure